Clinical laboratory testing and in vitro diagnostic test systems. Susceptibility testing of infectious agents and evaluation of performance of antimicrobial susceptibility test devices. Evaluation of performance of antimicrobial susceptibility test devices Part 2, (31st July 2007) - British Standards Institution,
No abstract available